2013
DOI: 10.22610/jebs.v5i8.429
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Customer’s Impulsivity and Marketing Cues to Purchase Decision of Beverage Product Category

Abstract: The research was conducted to explore consumer impulsivity and impulsive buying toward beverages product. In addition, in subsequent analysis, it also applies Consumer Decision Journey into impulsive buying behavior on beverage products. The analysis explains which marketing cues acts as most influential factors in such purchase behavior. Questionnaire was designed based on valid scale borrowed from previous research. A total of 105 respondents participated in this research. Questionnaire was distributed direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…With numerous RTD tea beverages currently available on the market (Lee and Liao, 2009) and new types of RTD tea beverage continually being introduced (Manufacturing Close-Up, 2013), it is imperative for tea marketers to increase their understanding of the attitudes and desires of RTD tea beverage consumers. Although numerous studies have examined beverage consumer behavior (Su, 2007;Prawono et al, 2013;Kim and House, 2014), few studies have focussed specifically on the motivation of RTD tea consumers as well as their underlying attitudes and desires. In addition, previous studies have shown that consumers tend to evaluate products according to product attributes (Richardson et al, 1994) such as price, color, brand, packaging, and sensory features (Min et al, 2012), which are the primary drivers of product success (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With numerous RTD tea beverages currently available on the market (Lee and Liao, 2009) and new types of RTD tea beverage continually being introduced (Manufacturing Close-Up, 2013), it is imperative for tea marketers to increase their understanding of the attitudes and desires of RTD tea beverage consumers. Although numerous studies have examined beverage consumer behavior (Su, 2007;Prawono et al, 2013;Kim and House, 2014), few studies have focussed specifically on the motivation of RTD tea consumers as well as their underlying attitudes and desires. In addition, previous studies have shown that consumers tend to evaluate products according to product attributes (Richardson et al, 1994) such as price, color, brand, packaging, and sensory features (Min et al, 2012), which are the primary drivers of product success (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%